Analisis Instalasi Listrik Gedung Untuk Lantai Lobby PT Bimoli - Abdul Kodir Albahar; Abdul Azis; Sri Hartanto (JURNAL ELEKTRO, 2025)
Electrical installation planning in a building is a vital aspect to ensure safety, efficiency, and operational comfort. This study aims to design an electrical installation system on the lobby floor of PT BIMOLI by referring to national standards such as PUIL 2011 and SNI. The methods used include a power requirement survey, calculation of active and apparent power, selection of distribution panel capacity, cable route planning, and determination of a protection system with MCB and grounding. The calculation results show a total power requirement of 63,675 Watts or 79,539 VA with a power factor of 0.8. After adding a 50% safety reserve, the required electrical capacity is 120 kVA. The installation design includes a single line diagram, wiring diagram, and calculation of cable requirements for lights, sockets, and air conditioners. The designed system meets aspects of energy efficiency, user safety, and applicable technical standards. The selection of 3x2.5mm² and 5x2.5mm² cables. Cable requirements for Downlights and TL Lamps ± 215 meters, cable requirements for 2pk AC ± 120 meters, cable requirements for 5pk AC ± 122 meters. Power distribution system, type of protection (MCB, grounding). Components such as downlights, TL lamps, NYM cables, as well as overcurrent and leakage current protection systems, have been adjusted to the characteristics and needs of office space. 3-phase MCB used for 5pk AC 16 Ampere, 1-phase MCB for 2pk AC 10 Ampere, 1-phase MCB used for TL Lamps and 4 Ampere Downlights, 1-phase MCB 32 Ampere Socket